3'UTR of tobacco vein mottling virus regulates downstream GFP expression and changes in host gene expression - Sun, Zhenqi; Liu, Dongyang; Li, Bin; Yan, Fangfang; Wang, Yuhu; Yang, Tianqi; Wang, Haijuan; Xu, Jiaxin; Zhou, Hongyou; Zhao, Mingmin (Frontiers in Microbiology, 2024)
Tobacco vein mottling virus (TVMV) is a member of the family Potyviridae. The 3' untranslated region (3'UTR) of viral genomic RNA has been reported to significantly impact viral infection. Nevertheless, the role of the TVMV 3'UTR during viral infection remains unknown.Here, a 3'UTR-GFP expression vector was transiently expressed in Nicotiana benthamiana, in which the 3'UTR of TVMV was introduced upstream of the green fluorescent protein (GFP) gene.Transcriptome sequencing was performed to analyze the genes associated with plant resistance.The effect of the TVMV 3'UTR on GFP expression was studied using an Agrobacterium-mediated transient expression assay, revealing that the TVMV 3'UTR significantly inhibited GFP expression. Transcriptome analysis of differentially expressed genes in 3'UTR-GFP in N. benthamiana was performed to elucidate the why the TVMV 3'UTR inhibited GFP expression. Eighty genes related to plant disease resistance were differentially expressed, including 29 upregulated and 51 downregulated genes. Significantly upregulated genes included those encoding the calcium-binding protein CML24, leucine-rich repeat receptor-like tyrosine-protein kinase, and respiratory burst oxidase homolog protein E. The significantly downregulated genes included calcium-binding protein 7, ethylene-responsive transcription factor 10, endoglucanase 5, and receptor-like protein kinase.